Strategic asset management of water supply and wastewater infrastructure : invited papers from the IWA Leading Edge Conference on Strategic Asset Management (LESAM), Lisbon, October 2007 - IWA Leading Edge Conference on Strategic Asset Management (3rd : 2007 : Lisbon, Portugal); Alegre, Helena, editor; Almeida, Maria do Cǔ (New york : IWA Pub., 2009)
FTIR